Spotlight on fluticasone furoate/umeclidinium/vilanterol in COPD: design, development, and potential place in therapy - Lal, Chitra (Int J Chron Obstruct Pulmon Dis, 2016)
COPD is characterized by persistent airflow obstruction caused by exposure to irritants including cigarette smoke, dust, and fumes. According to the latest GOLD (Global Initiative for Chronic Obstructive Lung Disease) guidelines, a combination of inhaled corticosteroids, long-acting β(2) agonists, and long-acting muscarinic receptor antagonists can be used for group D COPD patients who are at high risk for exacerbations. Umeclidinium/fluticasone furoate/vilanterol is one such triple-combination therapy currently under development with some completed and several ongoing clinical trials. This review paper summarizes the pharmacologic profiles of these medications and highlights findings from clinical trials, including safety and efficacy data, while speculating on the role of this therapy in current treatment for COPD.